PENGARUH PENGUNGKAPAN TANGGUNG JAWAB SOSIAL TERHADAP KOEFISIEN RESPON LABA - Muhammad Nurkholis, Carmel Meiden (Jurnal Akuntansi, 2018)
The purpose of this research is to measure the influence of disclosure corporate social affected to earnings response coefficients, especially in companies listed in Indonesia Stock Exchange in the year 2007-2011. Corporate Social Responsibility (CSR) disclosures is the independent variable of this research, with leverage and size as control variables. Measurement of CSR disclosures is based on the index Global Reporting Initiative (GRI) G3 2006. Object research used 7 companies in the Indonesia Stock Exchange (IDX) that have sustainability reports in the period 2007-2011, the end of the fiscal year or fiscal month December and has a publication date of the financial statements, with the total sample for five years as many as 35. Analysis technique used are F-Test, t-Test, and R2, and multiple regression analysis. CSR disclosures have positif effect to earnings response coefficient not significantly on α = 5% both model I and model II. In summary, the result of this research not found proper evidence that CSR disclosures has negative effect to earnings response coefficient. Keyword: Corporate Social Responsibility Disclosure, Earnings Response Coefficient, GRI